Changing of the spontaneous polarization in niobate nanoparticles induced by non isovalent doping - de Lima, Caio Vinicius [UNESP]; Lima Nobre, Marcos Augusto [UNESP]; Lanfredi, Silvania [UNESP] (Trans Tech Publications, 2015)
Ferroelectric niobates with tetragonal tungsten bronze TTB-type structure have shown great technology interest for application in pyroelectric detectors and piezoelectric transducers, sensor/filter in composite. The synthesis and structural characterization of the solid solution of iron doped potassium strontium niobate with stoichiometry KSr2(Fe0. 25Nb4. 75)O15-δ prepared by modified polyol method were carried out. The highest crystallinity was obtained for the precursor powder calcined at 1150ºC for 10 hours in oxygen atmosphere. The structural characterization was performed by X-Ray diffraction. The average crystallite size obtained was equal to 25 nm. The structural parameters were determined by Rietveld method giving a tetragonal system with space group P4bm. The spontaneous polarization of the solid solution was calculated, being equal to 39. 46 µC. cm-2. Polihedra distortion and its correlation with niobium off-center are discussed.
Keywords: Niobate; Spontaneous polarization; Tetragonal tungsten bronze structure